Translations not in the making? Rejections, disruptions and impasses in translator–publisher correspondence - Paloposki, Outi (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
This is a study of a frequently occurring but seldom studied phenomenon: that of proposed translations, rejections and disruptions in translators’ work. The study is based on the correspondence of 64 translators in the archive of the Werner Söderström (WSOY) publishing house in Finland between the 1880s and the 1940s. It deals with around 180 translator suggestions and an almost equal number of rejections discovered in translator–publisher correspondence. The research draws on actor-network theory and its focus is on emergent processes and controversies, exploring the events and decisions as they unfold in the archived interaction between translators and publishers. The large number of rejections, the various kinds of disrupted processes in the making of translations and the contingency of the translation event are set in high relief. Studying the way translations come into being – or do not come into being, as is often the case – shifts the focus from translations as products to the translation event: disruptions and impasses, it will be shown, constitute a significant share of translators’ and editors’ work and are crucial in understanding the translation process.